The Role of VKORC1 in Vitamin K Metabolism and Warfarin Sensitivity: A Narrative Review of Genetic and Clinical Perspectives - Ayoob Radhi Al-Zaalan; Hussam Saadi Aziz (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Warfarin (commonly known by its trade name, Coumadin) is an oral anticoagulant that has been widely used for the prevention and treatment of thromboembolic disorders. Despite its clinical benefits, warfarin therapy is complicated by a very narrow therapeutic index and wide inter-individual variability in dose requirements. This variability represents a major challenge for clinicians, as inappropriate dosing may lead to serious adverse outcomes such as bleeding or thrombotic events. A growing body of evidence suggests that genetic polymorphisms are among the most important factors contributing to this variability, particularly those involving the Vitamin K Epoxide Reductase Complex Subunit 1 (VKORC1) gene. VKORC1 encodes a key enzyme that functions as a bottleneck in the vitamin K cycle, playing an essential role in the regeneration of reduced vitamin K (VKH). This active form of vitamin K is required for the γ-carboxylation of vitamin K–dependent clotting factors, including prothrombin and other coagulation proteins. Polymorphisms within VKORC1 can significantly alter the enzyme’s expression and activity, thereby modifying an individual’s sensitivity to warfarin. One of the most clinically relevant variants is the -1639G>A (rs9923231) polymorphism, which reduces VKORC1 transcription and subsequently decreases enzyme activity. Patients carrying the A allele often exhibit increased sensitivity to warfarin and therefore require lower maintenance doses compared to those with the G allele. Understanding these genetic influences not only improves our knowledge of warfarin pharmacogenomics but also highlights the importance of personalized medicine in anticoagulant therapy. Incorporating VKORC1 genotyping into clinical practice could optimize dose prediction, minimize adverse events, and enhance the safety and effectiveness of warfarin therapy. This narrative review aims to provide an in-depth discussion of the complex role of VKORC1 in vitamin K metabolism and its impact on warfarin sensitivity, thereby underscoring the critical relevance of genetic factors in guiding individualized anticoagulation therapy.